Blood culture bottle shortage mitigation efforts: analysis of impact on ordering and patient impact - Christopher D. Doern; Melissa Whitman; Michelle Doll; Suzanne Lavoie; David Friedel; Gonzalo Bearman; Jeffrey Kim; Heather Masters; Susan Roseff; Jim Willis; Roxanne Mercer; Aaron Hill; et al. (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract